Surgical alternatives for closure of bucco sinus fistula: literature review (Research, Society and Development, 2022)
Oral and sinus communication (BCC) consists of the non-physiological space formed between the maxillary pebble and the oral cavity, which, if left untreated, will progress to an oroantral fistula or, even, chronic sinus disease. This article aims to review the literature on surgical alternatives for closure of oroantral fistula. For the construction of this work, a bibliographic survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. The practicing oral and maxillofacial surgeon who treats patients with oroantral communications must be familiar with and competent with the various treatment options available. Multiple techniques are available, from purely soft tissue flaps, which have proven successful over time, to a combination of hard tissue grafts (autologous, alloplastic, or allograft), which may be helpful with increasing demand for restorations. with implants. While different procedures have proven successful, all are premised on treating any underlying sinusitis, which is associated with an increased risk of recurrent OAC.